Highly Selective Photocatalytic Reduction of CO2 to CO Over Ru‐Modified Bi2MoO6. Issue 7 (13th April 2022) - Ren, Guangmin; Liu, Sitong; Li, Zizhen; Bai, Hongcun; Hu, Xiude; Meng, Xiangchao
Abstract : Photocatalytic CO2 reduction is a promising strategy for sustainable development. Optimizing the structure of photocatalysts to facilitate the separation of electron–hole pairs for improved performance is not only highly desirable but also challenging. Aiming to improve the photocatalytic reduction of CO2, Ru is selected and applied to modify Bi2 MoO6 . Compared to pure Bi2 MoO6, Ru‐Bi2 MoO6 exhibits substantially excellent photocatalytic activity in CO2 reduction with CO generation of 142.77 μmol −1 g −1 and selectivity of 100% under simulated sunlight. The enhancement might be attributed to the following: 1) Ru 0 acting as an electron acceptor facilitates unique interaction and activation with CO, 2) Ru 4+ doping enhances light absorption with addition impure energy levels within the bandgap, 3) ultrathin layers is in favor of improving the specific surface area and providing more exposed sites for CO2 adsorption and activation, and 4) interfaces between Ru and Bi2 MoO6 accelerate charge transfer and separation, and electrons and holes are efficiently transferred to Ru and Ru 4+, respectively, facilitating the reduction and oxidation reactions. This work provides a new approach to improve photocatalytic CO2 abatement and further presents valuable new insights into the design modification of photocatalytic systems. Abstract : Ru‐modified Bi2 MoO6 has been successfully prepared using a one‐step solvothermal method. As‐prepared samples exhibit excellent photocatalytic activity in CO2 reduction, with CO generation of 142.77 μmol −1 g −1 and selectivity of 100% under simulated sunlight.